THE INFLUENCE OF GENDER ROLES ON FAMILY RELATIONS - Mirzaeva Sarvinoz Shukhratjon kizi (Western European Studies, 2024)
This article examines the influence of gender roles on family relations in the context of modern socio-cultural changes. Traditional ideas about gender roles and their evolution in the 20th and 21st centuries are analyzed, which influenced the structure of family life. Positive and negative aspects associated with changes in gender roles are discussed, including equality in relationships, the emergence of conflict, and parenting. Special attention is given to how modern families are adapting to new realities, creating more equal and harmonious relationships. It concludes by emphasizing the importance of understanding the uniqueness of each family and the need for a flexible approach to gender equality
Keywords: Gender roles; family relations; equality; child rearing